Barriers Against Hepatitis B Vaccination in High-Risk Adults: A Cross-Sectional Study - Aslan, Abdullah; Şaşmazer, Başak; Ayar, Yasin; Duran, Zeynep Cansu; Akova, Murat (Turkish Journal of Gastroenterology, 2022)
Background: The hepatitis B vaccination has been strongly recommended by regulatory bodies. However, there are great discrepan- cies between routine practices and the recommendations of regulatory agencies in many countries. We aimed to identify the barriers against Hepatitis B Vaccination (HBV) for high-risk patients by comparing the awareness, attitude, and knowledge among vaccinated and unvaccinated patientsMethods: A 34-item questionnaire was applied to 156 patients, consisting of renal transplant recipients, allogeneic hematopoietic stem cell transplant recipients, and patients with chronic hepatitis C. Multiple logistic regression analysis was employed to identify indepen- dent predictors for patients receiving the hepatitis B virus vaccination.Results: The multiple logistic regression analysis revealed that the independent risk factors against the HBV vaccination were a require- ment of a separate appointment for hepatitis B virus vaccination (aOR: 3.35, 95% CI, 1.18-9.47), and fear of severe side effects that can be related with hepatitis B virus vaccination (aOR: 3.67, 95% CI, 1.18-9.47). However, taking a recommendation for hepatitis B virus vaccination at least once from a health care provider (aOR: 0.04, 95% CI, 0.01-0.11), and having a health insurance (aOR: 0.09, 95% CI, 0.01-0.55) were independent protective factors for being vaccinated. In further analysis among patients with at least a single dose of vaccine, the lack of recommendation from a health care provider for hepatitis B virus vaccination and the absence of a healthcare pro- vider who is responsible for monitoring the completion of the 3-dose vaccination were identified as independent risk factors for failure to complete the 3-dose hepatitis B virus vaccination.Conclusion: In high-risk adults, the barriers against hepatitis B virus vaccination should be handled by a comprehensive action plan to achieve the WHO 2030 hepatitis elimination target.